THE ROLE OF FARMERS IN THE ECONOMY AND PROSPECTS FOR THEIR DEVELOPMENT IN UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2022)
The article covers the role of peasant farms in the economy and prospects of their development in Uzbekistan. Peasant farms play an important role in solving the food problem.